THE ROLE OF DEMOGRAPHICS IN DETERMINING RISK TOLERANCE FOR DERIVATIVES INVESTORS - Vyshnavi A; M. N. Periasamy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the role of demographic factors—age, income, and education—in determining risk tolerance among derivativesin India. The primary research questions focus on how these demographic variables influence an investor’s willingness to take risks in derivatives trading. The objectives are to understand the relationship between demographic characteristics and risk tolerance, assess the predictive power of each factor, and provide insights into how demographic attributes can inform investment strategies. A quantitative approach using a binary logistic regression model was employed, based on a sample of 384 investors. Descriptive statistics, ANOVA, and regression analysis were applied to evaluate the data. The results indicate significant relationships between age, income, and education with risk tolerance, with younger, higher-income, and more educated investors showing greater risk tolerance. The findings suggest that demographic characteristics are key determinants of risk behaviour in financial markets. The study recommends that financial advisors tailor investment strategies based on the demographic profiles of clients, while financial institutions may benefit from incorporating these insights into their products and services. Limitations include the use of a Likert scale and a sample that may not be fully representative of the broader population. Future research could explore additional demographic variables and longitudinal studies to gain deeper insights into evolving risk tolerance over time.